Equilibrium solubility determination, modelling and preferential solvation of bioactive iminodibenzyl in aqueous co-solvent mixtures at various temperatures. (May 2019) - Li, Xinbao; Liu, Yinping; Farajtabar, Ali; Ding, Guangxuan; Chen, Gaoquan; Zhao, Hongkun
Graphical abstract: Highlights: Iminodibenzyl solubility in four cosolvent + water mixtures was determined. Iminodibenzyl solubility was correlated using the Jouyban-Acree model. Preferential solvation of iminodibenzyl was studied by using the IKBI method. Abstract: The mole fraction solubility of bioactive iminodibenzyl in aqueous co-solvent mixtures of ethanol, ethylene glycol (EG), dimethyl sulfoxide (DMSO) and isopropanol was examined by the saturation shake-flask method over the temperature range from 283.15 K to 328.15 K at pressure of 101.2 kPa. The experimental solubility increased with increasing temperature at a given co-solvent composition and decreased with the increasing mass fraction of water in each binary system. The maximum solubility was found in pure co-solvent. Given the same temperature and mass fraction of the co-solvent, the solubility of iminodibenzyl was greater in (DMSO + water) than in the other three co-solvent systems. The solid crystal examples of iminodibenzyl was tested by X-ray power diffraction showing no polymorphic transformation, solvate formation or crystal transition during entire experiments. The Jouyban-Acree model was employed to correlate the measured solubility. The calculated data were in alignment to measured values and RAD and RMSD data were no more than 3.08% and 10.37 × 10 −4, respectively. Furthermore, quantitative values for the local mole fraction of ethanol (EG, DMSO or isopropanol) and water around the iminodibenzyl were acquired by using the Inverse Kirkwood–Buff integrals method. The preferential solvation parameters for ethanol, EG, DMSO or isopropanol were positive in the four co-solvent mixtures in intermediate and co-solvent-rich compositions, which indicated that iminodibenzyl was preferentially solvated by the co-solvent. iminodibenzyl could act mainly as a Lewis acid interacting with proton-acceptor functional groups of the co-solvents.